BRANDING MASJID ERA DIGITAL: INOVASI KONTEN KREATIF UNTUK MENINGKATKAN KETERLIBATAN REMAJA DI DESA KARYAMEKAR, KAB. GARUT - Abadi, Ferryal; Santos Winarso Dwiyogo; Nurdin; Badriyah; Mega Sukmawati (JURNAL ABDIMAS PLJ, 2025)
One way to restore the prosperity and vitality of mosques is to begin by reorganizing and rebuilding the mosque’s branding, modeled after the Prophet Muhammad’s mosque. Various methods can be employed to revive the vibrancy of nearby mosques,such as holding islamic study sessions featuring prominent figures to attract the interest of the younger generation and the general public. A youth – led management team, strong internal solidarity, and a strategic location are key strengths in implementing branding strategies. Furthermore, the use of digital platforms can support mosque activities and enhance the mosque’s image among the public. In today’s digital era, digital platforms are crucial for accessing information and disseminating positive values. This PkM activity si expected to demonstrate the social awareness of youth in bulding mosque branding through creative social media content and increasing creativity in developing ideas for disseminating religious values.